Meylida Analysis of Determinant Factors of Smoking Behavior in Adolescents - Meylida Swatitis Kurnia Saputri; Syamsulhuda Budi Mustofa; Daru Lestantyo (Indonesian Journal of Global Health Research, 2026)
Smoking behavior is a serious health problem among adolescents in Semarang City, with initiation at an early age influenced by various individual and environmental factors. To analyze the determinants that influence smoking behavior among junior high school and vocational high school students in Tembalang District, Semarang City. This was an analytical observational study with a cross-sectional design. The population comprised 248 junior and vocational high school students in Tembalang, selected via saturated sampling. Primary data were collected using a questionnaire tested for validity (r>0.312) and reliability (Cronbach's Alpha > 0.6). The research results showed that the majority of respondents were in the early adolescent category (15-19 years) at 85.9%, the majority of respondents had a positive attitude at 55.2%, respondents who received easy access were 76.6%, while respondents who did not receive smoking support were 54.8%. Bivariate analysis showed a significant relationship between smoking behavior and age, attitudes, and ease of access (p<0.05), while social variables showed no significant relationship (p>0.05). All variables examined in this study were shown to have a significant relationship with smoking behavior, apart from social variables which did not show any significant relationship.